Focus group discussion on psycho-physical training, physical training and psychological training among Malaysia university students' athlete - Sulaiman, Tajularipin; Abdullah, Muhammad Nazrul Hakim; Wan Jaafar, Wan Marzuki; Motevalli, Saeid (SEAAIR Secretariat, 2024)
The impact of psycho-physical training, physical training, and psychological training is crucial in developing professional athletes, but the perception and understanding of these trainings in particular has been relatively ignored. For example, prior to this research the understanding of these trainings was more on instructions and paper-pencil test. Thus, the aim of this research was to explore the experiences of young university student-athletes towards the psycho-physical training, physical training and psychological training throughout their athlete’s career. The idea, factors and components of each training should not be overlooked especially in the populations of young university athletes, as they are exposed to more psychological risks associated with the nature of their career such as stressful and tensed competitive circumstances, monotonous training, academic works and interpersonal conflict factors. There are three (3) themes concluded from each training in exploring the ideas, components they found and factors in improving for each training. This research on young university athletes enables future research to develop module in creating new insight and awareness in contribute practical strategies and techniques to be implemented for sports psychologists, counsellors, and educational authorities. Such efforts definitely assist more young university athlete by inventing early prevention strategies to improve the educational environment and contribute towards the athletes’ performance.